PENGARUH NILAI-NILAI GURU TERHADAP KOMPETENSI PEDAGOGIK GURU - Novitri, Safriani; Rizqiani, Diyah Ayu; Ramadhan, Syahrul; Mukhaiyar, Mukhaiyar; Bulan, Linda Sari (Wahana Literasi: Journal of Language, Literature, and Linguistics, 2023)
Science is something commonly used worldwide and especially in the field of education. Suitable with teaching methods, science will be transferred to the students by the teachers. The need for better results on the educational system and educational evaluation in Indonesia requires a good quality of the educators of course in this phenomenon is the teachers. The professional teacher's personality is a combination of who the teacher is and the teachers are as educators. It means that teachers' capabilities and mindsets will affect the transfer of science to the students. The priority of this target is to get information about the value of English teachers in the Islamic Elementary School of Madrasah Ibtidaiyah Pekanbaru (n=6), which teaches at five schools in Pekanbaru. The questionnaire and observation were given by representing the profile of the teachers, including educator requirements, teachers’ competence, professional graduation, and the teachers’ attitude. And how well the English teachers have the component to transfer knowledge and guide the students to learn English, as we know well that English is a communication language. This survey aims to determine how teachers meet the standards set out in UU No. 14 of 2005 for the Teaching Profession.